Adsorption of dye on carbon microparticles: physicochemical properties during adsorption, adsorption isotherm and education for students with special needs - Rina Maryanti,; Nandiyanto, Asep Bayu Dani; Manullang, Tryastuti Irawati Belliny; Hufad, Achmad; Sunardi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to demonstrate the adsorption of dye on carbon microparticles. We conducted two experiments: Understanding of the adsorption of dye on carbon microparticles. We used turmeric solution as a model of dye, in which this solution was contacted into commercially available carbon microparticles in the batch-typed adsorption reactor. The measurement results were then compared to several adsorption isotherm models, such as Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich models; and finding teaching strategies to improve students’ understanding on the adsorption concept to students with special needs. As for the second part which is finding strategies to teach the obtained results and their concept of adsorption to students with special needs, we evaluated the strategies to eight students with intellectual disabilities in special schools in Kuningan District, Indonesia using a Single Subject Research method (equipped with pre-test, post-test, and experimental demonstration). The results showed that carbon can absorb dye and can be used as an alternative for wastewater treatment. The isotherm models have the linearity parameter R2 of above 50%, and the most suitable model is Freundlich. The models also confirmed favorable adsorption with multilayer structure and physical interaction between turmeric and carbon microparticles. Demonstrating experiments and informing the measurement results gave great impacts on students’ comprehension, in which they have better understanding about the concept of adsorption compared to the conventional teaching method.